METHOD OF ENCODING OF SEQUENCE OF SHOTS FOR PROVIDING OF AVAILABILITY AND INTEGRITY OF DYNAMIC VIDEORESOURCE - Barannik, Vladimir; Parkhomenko, Maksym; Barannik, Natalia; Hahanova, Anna (Ukrainian Information Security Research Journal, 2023)
In the article grounded presence impressionable factors in relation to the loss of general efficiency of information technology of treatment and transmission of dynamic videoresource, that results in the decline of level of semantic integrity and availability of information. It is rotined that such factors touch the following: in the process of forming of code values for the aggregate of position co-ordinates of splyn frames there can be cases of repletion of the set length of code combination; there is a requirement in the additional forming of amount of bats of official information, namely on the additional use of markers: location of sequences of position co-ordinates which code values are formed for; between the code constructions of nearby aggregate of position coordinates. The basic stages of creation of technological conception of integration of the created methods of treatment of V-R of shots are expounded in information technology of treatment and transmission of dynamic videos of resources, which is based on the removal of vulnerable factors of loss of efficiency of functioning of ITOPDV on the basis of the created recurrent technology of encoding of variable aggregate of position coordinates in the bipolar mixed multiadical space on the basis of property of independence of gravimetric coefficients.